Two-Parameter Electronic Devices Quality Models - Eidukas, D.; Kalnius, R. (Elektronika ir Elektrotechnika, 2010)
Continuous control main probability characteristic modeling methods for multiparameter electronics devices has been made, when separate independent device parameters defect level probabilistic distributions are “a priori” known. Defected devices flow in control operation is targeted to localized repair operation in this stage, then devices with second type errors goes again into control and “rotates” until all devices are accepted as good. Second type classification errors probabilities (defect device is accepted as good) in control and repair operations are described by one generalized error model, which is used in linear defect level transformation by different parameters. For all device defect level transformation, defect level transformation by different parameters is used. For all defect level transformation, defect levels densities by different parameters combination, is used referencing by transformation model. It is offered to use approximated models instead of exact whole device defect level probabilistic density by different parameters, described by beta law density, because it is the whole model and the exact defect level density is expressed by many different models in every partial interval of integration. This method simplifies modeling procedure, without decreasing engineering analysis accuracy.